2021
DOI: 10.1115/1.4053178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fault Modeling in the Identification of Bearing Wear Severity

Abstract: Recent research into machines involved in the power generation process has demanded deep investigation of model-based techniques for fault diagnosis and identification. The improvement of critical fault characterisation is crucial in the maintenance process effectiveness, hence in time/costs saving, increasing performance and productivity of the whole system. Consequently, this paper deals with a common fault in hydrodynamically lubricated bearings assembled in rotating systems, namely, that of abrasive wear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They reported an increase in journal-worn bearing vibration amplitude due to the bearing wear. Alves et al [21,22] developed a model to describe wear in journal-hydrodynamic bearings. They used temperature and the system vibration spectral analysis to determine the severity of wear in plain bearings and concluded that wear increments the system anisotropy.…”
Section: Of 26mentioning
confidence: 99%
“…They reported an increase in journal-worn bearing vibration amplitude due to the bearing wear. Alves et al [21,22] developed a model to describe wear in journal-hydrodynamic bearings. They used temperature and the system vibration spectral analysis to determine the severity of wear in plain bearings and concluded that wear increments the system anisotropy.…”
Section: Of 26mentioning
confidence: 99%
“…They reported an increase in journal-worn bearing vibration amplitude due to the bearing wear. Alves et al [24,25] developed a model to describe wear in journalhydrodynamic bearings. They used temperature and the system vibration spectral analysis to determine the severity of wear in plain bearings and concluded that wear increments the system's anisotropy.…”
Section: Introductionmentioning
confidence: 99%